Persepsi Mahasiswa Terhadap Pentingnya Mata Kuliah Akuntansi Forensik Sebagai Pengajaran di Perguruan Tinggi (Studi Pada Universitas Nahdlatul Ulama Nusa Tenggara Barat) - Solatiyah, Baiq; Yakub, Muhammad (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2024)
This research aims to determine the perceptions of students majoring in Economics Islamic Faculty of Economics, Nahdlatul Ulama University, West Nusa Tenggara regarding interest and understanding of forensic accounting courses in the learning curriculum majoring in Islamic economics. This study is a qualitative research conducted using the interview method as evidence collection. Participants in this research consisted of students from the classes of 2021 and 2022 who had studied forensic accounting courses. The process of data analysis in this research involves data collection, data reduction, data presentation, and conclusion drawing. The findings of the research indicate that the perception in terms of student interest in forensic accounting gives a positive response, namely that they consider the forensic accounting course to be very interesting and important as learning in the Islamic economics department, while the student's perception in terms of understanding shows that the forensic accounting course is very easy to understand even though there are There are also students who have the nation that forensic accounting courses are extremely challenging to comprehend.